Pemanfaatan Algoritma Generate and Test Dalam Kasus Travelling Salesman Problem Pencarian Jalur Terpendek - Algifanri Maulana (STMIK Budi Darma, 2021)
The Generate and Tesr algorithm is a very simple method in a heuristic search. The completion process of this algorithm is a combination of depth-first search with backtracking because the solution must be generated completely before testing. systematically and following procedures will find a solution. The problem in this study is that if the problem discussed in the Generate test algorithm is very broad, it takes a long time to solve it. The main purpose of this study is to find the shortest alternative route to find a solution in order to obtain the smallest route so as to save transportation costs. The final result of this study obtained 8 paths to the final destination, 2 paths that have the shortest route, namely the A-C-F-I-T and A-C-E-G-T routes. So that the tests carried out can pass through 2 paths to be able to visit the city.